Engineering biosynthetic enzymes for industrial natural product synthesis. Issue 8 (4th May 2020) - Galanie, Stephanie; Entwistle, David; Lalonde, James
Abstract : This review describes examples of the broadening industrial relevance of engineered secondary metabolism enzymes, natural products and analogs being made with these enzymes, and technology improvements that have enabled their development since 1999. Abstract : Covering: 2000 to 2020 Natural products and their derivatives are commercially important medicines, agrochemicals, flavors, fragrances, and food ingredients. Industrial strategies to produce these structurally complex molecules encompass varied combinations of chemical synthesis, biocatalysis, and extraction from natural sources. Interest in engineering natural product biosynthesis began with the advent of genetic tools for pathway discovery. Genes and strains can now readily be synthesized, mutated, recombined, and sequenced. Enzyme engineering has succeeded commercially due to the development of genetic methods, analytical technologies, and machine learning algorithms. Today, engineered biosynthetic enzymes from organisms spanning the tree of life are used industrially to produce diverse molecules. These biocatalytic processes include single enzymatic steps, multienzyme cascades, and engineered native and heterologous microbial strains. This review will describe how biosynthetic enzymes have been engineered to enable commercial and near-commercial syntheses of natural products and their analogs.